Joint consideration of energy expenditure, air quality, and safety by cyclists. (October 2018) - Bigazzi, Alexander Y.; Gehrke, Steven R.
Highlights: Three concerns of urban cyclists are examined with structural equation modelling. Cyclists vary significantly in their consideration of energy expenditure. Traffic safety and air pollution risks are perceived differently by cyclists. Energy and air quality concerns are significantly associated with each other. Abstract: Public health benefits are an important motivator and justification for urban cycling promotion. The health impacts of cycling are typically evaluated using three main effect pathways: physical activity (exercise), air pollution exposure, and safety (crashes). Effects of safety on cycling behaviour have been investigated, but little is known about how energy expenditure and air quality concerns influence cycling decisions. Understanding cyclist perceptions and preferences is important for planning and designing sustainable and healthy transportation networks. As such, research providing insights into the heterogeneity of these concerns is needed to inform models of behavioural change with evolving vehicles, technology, and infrastructure. The objective of this paper is to investigate the joint consideration of energy expenditure, air quality, and safety concerns by cyclists, and their relationships with cycling frequency. A structural equation model is developed based on data from a survey of 625 intercepted real-world cyclists. Air quality and energy expenditure were considered in routing decisions by 51% and 73% of the cyclists, respectively. Model results show that traffic safety and air pollution risks are perceived differently by cyclists, which has implications for modeling urban cycling behaviour in the context of evolving motor vehicle fleets. Safety concerns were associated with less frequent cycling, but not air quality concerns. Consideration of energy expenditure varies significantly among individuals and trip types, which will emerge with different preferences related to hills, stops, speeds, and electric-assistance. Energy and air quality concerns were significantly associated, suggesting health-conscious cyclists who tended to be older, have higher educational attainment, be more physically active, and cycle more recreationally. Utilitarian and recreational cycling trips had different relationships with health-related considerations and with weekly physical activity.